2018
DOI: 10.18502/kss.v3i3.1871
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Crowdfunding Model as an Alternative Funding Source for Micro, Small, and Medium-Scale Businesses in Various Countries

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Campaign duration does not have a significant effect on the success of crowdfunding campaigns, which is not in line with H1c. This result is supported by Wati and Winarno who found that the fundraising period does not significantly affect the success of crowdfunding campaigns (Wati and Winarno 2018). Periods of time that are too long can be considered annoying because it is difficult to focus on achieving its goals at the right time (Lunenburg 2011).…”
Section: Methodsmentioning
confidence: 92%
“…Campaign duration does not have a significant effect on the success of crowdfunding campaigns, which is not in line with H1c. This result is supported by Wati and Winarno who found that the fundraising period does not significantly affect the success of crowdfunding campaigns (Wati and Winarno 2018). Periods of time that are too long can be considered annoying because it is difficult to focus on achieving its goals at the right time (Lunenburg 2011).…”
Section: Methodsmentioning
confidence: 92%
“…1. The Crowdfunding business model that here are many success measures for a crowdfunding platform (please see [27], [7] [20] [11] [12] [28][25] [7]) for a comprehensive success measure literature), we focus on using the success rate as the percentage of entrepreneurs who have applied for crowdfunding and managed to be successful in getting their required funds. The remaining of this paper is organized as follows: in the next section we present the development process of an agent based model, the section three introduces the proposed model, the section four shows some results of the study, last but not least the section five provides a conclusion and some perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…MSMEs can access sources of funding internaly and externaly. Internal funding sources come from personal savings, family and friends (Wati & Winarno, 2018). External sources of funding come from bank loans, leasing and venture capital providing larger amounts of fund (Fahmi, 2014).…”
Section: Introductionmentioning
confidence: 99%